2019
DOI: 10.3390/ijerph16081472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship between Well-Being and Living with a Dog for People with Chronic Low Back Pain: A Feasibility Study

Abstract: Chronic low back pain is a significant societal and personal burden that negatively impacts quality of life. Dog ownership has been associated with health benefits. This study evaluated the feasibility of surveying people with chronic low back pain to assess the relationship between dog ownership and well-being. A mail-out survey was sent to 210 adult patients with chronic low back pain. Measures of quality of life, pain, physical activity, emotional health, social ties and dog ownership were included. Feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 78 publications
(102 reference statements)
1
18
0
Order By: Relevance
“…Regarding pain intensity, Gordillo et al obtained similar results to ours in that most patients with chronic pain report that they had moderate to severe pain [53]. Another recent study suggests that dog ownership provides relief and support for chronic lower back pain [54]. In a study of 382 outpatients of a Pain Unit, Marcus et al [35] showed that the presence of therapy dogs in the waiting room could significantly reduce pain and emotional stress, and improve emotions and feelings of well-being among the family, companions, and health professionals.…”
Section: Discussionsupporting
confidence: 70%
“…Regarding pain intensity, Gordillo et al obtained similar results to ours in that most patients with chronic pain report that they had moderate to severe pain [53]. Another recent study suggests that dog ownership provides relief and support for chronic lower back pain [54]. In a study of 382 outpatients of a Pain Unit, Marcus et al [35] showed that the presence of therapy dogs in the waiting room could significantly reduce pain and emotional stress, and improve emotions and feelings of well-being among the family, companions, and health professionals.…”
Section: Discussionsupporting
confidence: 70%
“…It has been proposed that dogs influence mental well-being by modulating the human physiological response to stress, specifically via attenuation of the hypothalamic-pituitary-adrenal (HPA) axis and heart rate response to stressors [ 8 , 9 ]. Living with a dog may be associated with improved well-being for people with chronic pain [ 10 ]. The human-dog relationship is influenced by both canine and human characteristics [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carr et al [16] Dog ownership and its impact on people with chronic low back pain Dog owners reported fewer depression and anxiety symptoms, more social ties than non-dog owners, and improved well-being.…”
Section: Kogan Et Al [6]mentioning
confidence: 99%